Examining changes in social care referrals during the 2021 Winter Storm Uri in the Unite Texas network - Zackery White; Amanda Terry; Gillian Feldmeth; Alyssa Altstaedter; Halima Ahmadi-Montecalvo (Discover Public Health)
Abstract Objective Winter Storm Uri resulted in widespread power outages and safety hazards across Texas. As social needs are expected to increase during environmental hazards, technology-assisted social care coordination provides one strategy to support this influx; therefore, it is critical to record how they have been used during these natural hazards. Methods A retrospective analysis of Unite Texas social care data from January 12 to March 23, 2021, assessed the distribution of social needs and examined daily case counts, 30-day resolution rates, and closure times before, during, and after the storm. Results In the week leading up to the storm, daily case volume increased by 60.4%, with food assistance referrals rising to an average of 11.29 per day, compared to 1.70 per day during baseline conditions. However, during the storm itself, overall daily cases declined by 51.9% relative to pre-storm baseline levels. Following the storm, case rates returned to pre-storm levels, with increased case resolution and reduced time to case closure. Conclusion Technology-assisted care coordination may enhance social system resilience by enabling proactive responses to emerging needs before disasters and supporting efficient adaptation during recovery. Real-time visibility into both client needs and service availability allows for dynamic resource alignment, helping organizations respond more effectively to rapidly changing conditions. Future research should investigate whether these patterns reflect intentional, proactive coordination decisions versus incidental network activity, assess their consistency across different hazards and networks, and evaluate client and provider satisfaction with the referral process and outcomes.